The entry of black people through the ethnic-racial quota system at Ifes Vitória campus - Sebim, Charlini Contarato; Guimarães , João Vitor Ramos (The ESPecialist, 2024)
This research is part of a case study that sought to analyze the access of black students to technical courses integrated into secondary education offered by Ifes, Vitória campus. The time frame goes from 2012, the year of publication of Law 12,711 related to ethnic-racial quotas, until 2018, after 6 years of its validity. Our theoretical framework is based on Munanga (1999 and 2001) and Feres Júnior et al. (2018). Documentary analysis and bibliographical research show that the aforementioned law made it possible to increase access for black people to the Federal Education System. However, the ethnic-racial quota policy has not yet managed to provide equity if we compare the number of blacks and whites in Espírito Santo society and the entry of these groups into Ifes, campus Vitória.